Tragizm w powieści Borysa Pasternaka „Doktor Żywago” - Zbyrowski, Zygmunt (Studia Rossica Posnaniensia, 2015)
The novel titled Doctor Zhivago presents a number of tragic situations, conflicts and protagonists. The causes of tragedy can be objective (the war and revolution) or subjective (the characters’ personalities as well as their attitudes, views and decisions). Upon numerous occasions, these causes are linked and enhance one another, thus intensifying the tragic qualities that affect the fate of individuals and large groups alike. It is not only particular protagonists that suffer and perish; whole villages or army and partisan detachments share the same plight. Pasternak demonstrated that tragedy is a prominent and inevitable component of human life.